Strategi Marketing Public Relations X Motorcycle - Muhammad Nur Ilham; Maya Amalia Oesman Palapah (Jurnal Riset Public Relations, 2022)
Abstract. A company really needs the role of Marketing Public Relations to compete with its competitors. One of them is a business company in the field of fashion, namely CV. Bi-Ensi Fashionindo. In introducing one of its brands, namely FMC SpeedSupply, Marketing Public Relations conducted a program by participating in automotive events in the country and abroad. The event organized by FMC SpeedSupply is a national BBQ Ride event. With this event, Public Relations FMC SpeedSupply has a goal, namely to build Brand Awareness in the eyes of consumers. The purpose of this research is to find out how the strategies, barriers and evaluation of Marketing Public Relations through the “BBQ Ride” event conducted by FMC SpeedSupply in building Brand Awareness. The theory used in this study is three ways, namely pull, push, and pass. This research was structured using qualitative methods with a case study. While the data collection techniques were conducted by interview, observation, literature study and documentation. The results of this study found that in organizing the "BBQ Ride" event, there were several points that were explained, namely planning a strategy to determine goals, time of activities carried out, then determining the target public, then collaborating with several international and local brands. strategies to attract consumer interest and the results of the “BBQ Ride” event. There is a media optimization used by FMC SpeedSupply, namely FMC SpeedSupply using baligho media installed in several corners of the city of Bandung and using Instagram social media where Instagram has the Instagram business feature, feeds and stories to maximize its promotion. As for the obstacles and how FMC SpeedSupply overcomes them and the evaluation of FMC SpeedSupply in organizing this “BBQ Ride” event. Meanwhile, the reason why FMC SpeedSupply chose to hold the “BBQ Ride” event was to introduce this brand to the public and build brand awareness. Asbtrak. Suatu Perusahaan sangatlah membutuhkan peran Marketing Public Relations untuk bersaing dengan kompetitornya. Salah satunya adalah perusahaan bisnis di bidang fashion, yaitu CV. Bi-Ensi Fesyenindo. Dalam memperkenalkan salah satu brandnya yaitu FMC SpeedSupply, Marketing Public Relations melakukan program dengan mengikuti event-event otomotif yang ada didalam negeri maupun luar negeri. Event yang diselenggarakan FMC SpeedSupply adalah event nasional BBQ Ride. Dengan adanya event tersebut, Public Relations FMC SpeedSupply memiliki tujuan yaitu membangun Brand Awareness di mata konsumen. Tujuan adanya penelitian ini untuk mengetahui bagaimana strategi, hambatan dan evaluasi dari Marketing Public Relations melalui event BBQ Ride yang dilakukan oleh FMC SpeedSupply dalam membangun Brand Awareness. Teori yang digunakan dalam penelitian ini yaitu Three ways yaitu pull, push, and pass. Penelitian ini disusun menggunakan metode kualitatif dengan pendekatan studi kasus. Sedangkan teknik pengumpulan data dilakukan dengan wawancara, observasi, studi pustaka dan dokumentasi. Hasil dari penelitian ini ditemukan bahwa dalam menyelenggarakan event “BBQ Ride” tersebut ada beberapa poin yang dijelaskan yaitu merencakakan strategi menentukan tujuan, waktu & kegiatan yang dilakukan, lalu menentukan publik sasarannya, lalu bekerjasama dengan beberapa brand internasional maupun lokal, strategi menarik minat konsumen dan hasil dari event “BBQ Ride”. Terdapat optimalisasi media yang dimanfaatkan FMC SpeedSupply yaitu FMC SpeedSupply menggukan media baligho yang dipasang dibeberapa sudut kota Bandung dan menggunakan media sosial Instagram dimana Instagram memiliki fitur Instagram business, feeds dan story untuk memaksimalkan promosinya. Adapun hambatan dan bagaimana FMC SpeedSupply menanggulanginya serta Evaluasi FMC SpeedSupply dalam menyelenggarakan event “BBQ Ride” ini. Sedangkan alasan FMC SpeedSupply memilih menyelenggarakan event “BBQ Ride” untuk memperkenalkan brand ini kepada masyarakat dan membangun brand awareness.